Social Emotional Learning (SEL) - Husaj, Shqipe (European Journal of Multidisciplinary Studies, 2016)
Being in an environment for the first time, meeting strange people is not easy and simple for everyone. Some people need help in controlling its own emotions or the others emotions and feelings. This help can come from the parents at home, teachers and classmates at school or colleagues at working place. The aim of this paper is to discuss the importance of Social Emotional Learning ( SEL), its competences, skills involved in it etc. As SEL helps develop understanding and empathy, in this paper we will discuss the importance of empathy and some tips how to develop it.
Keywords: Social emotional Learning, feelings, empathy, skills etc.